Money Laundering - Seljmonaj, Agnesa (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Money laundering is the process of disguising the illegal origin of money or property from crime. Money laundering is a global problem that has side effects on the economic, political, security and social structure of the country. Consequences of money laundering are: undermining stability, transparency and efficiency of the financial system of the country, economic disturbances and instability, threat to the reform program, reducing investment and loss of reputation of the state. States are developing systems to combat money laundering in accordance with the specifics of their legal, economic and commercial systems. Money laundering is an exceptional threat to the integration of financial institutions, leading to disadvantaged entities which operate legally. Launderers do not generally seek to achieve the highest rate of return on the money that opera, but they were in an important position or investments that will allow them the easiest and quickest processing of money. A typical money laundering process has three stages: placement, layering and integration. In order to combat money laundering, a number of international conventions were adopted, giving rise to the adoption of national strategies to combat money laundering, as well as the criminalisation of money laundering as a separate criminal offence. The Criminal Code of the Republic of Serbia provided money laundering as a criminal offence, and the passing of the Law on Prevention of Money Laundering. This paper is a modest contribution to the analysis of money laundering.